Evolution patterns of detonation gas under different initiation positions in cylindrical charges - Meng REN; Zhongwen YUE; Xingyuan ZHOU; Qingyu JIN; Peng WANG; Shengnan XU (Meitan xuebao)
Improving the utilization efficiency of explosive energy is a crucial research topic in rock blasting. Detonation gas plays a significant role in borehole blasting, yet there is limited research on the evolution patterns of detonation gas from cylindrical charges. Utilizing an explosion schlieren experimental system, experiments on cylindrical charges were conducted to analyze the evolution patterns of detonation gas under different initiation positions. The results show that the evolution process of the detonation gas from the cylindrical charge can be divided into three stages: expansion, flow, and free diffusion. The distribution characteristics of detonation gas from cylindrical charges are determined by the number and propagation direction of detonation waves. When the initiation occurs at the apex, the gas flow field is formed by a single detonation wave. In contrast, initiation at the midpoint or one-third of the charge length results in a gas flow field formed by the superposition of two oppositely moving detonation waves. The distribution characteristics of the superimposed flow field depend on the momentum of the flow fields before superposition, which fundamentally explains how initiation position influences the distribution characteristics of detonation gas. The detonation gases flow towards the initiation point, resulting in a convergence effect. With apex initiation, gas converges at the initiation position due to the counter pressure of air, forming an convergence region. With midpoint initiation, two gas flows of equal momentum converge at the initiation position, their axial momenta canceling out to form an convergence region. With one-third point initiation, two gas flows of different momenta converge at the initiation position, forming an convergence region, with the higher momentum flow continuing to move axially through the convergence region. The convergence effect order based on initiation position is: midpoint initiation > one-third point initiation > apex initiation, with the maximum radial flow distance of the gas following the same order. This convergence effect of detonation gas promotes radial gas flow in the convergence region, resulting in the radial flow distance at the initiation position being much greater than at other positions.